Comparison of Presplit and Smooth Blasting Methods for Excavation of Rock Wells - Zilong Zhou; Ruishan Cheng; Xin Cai; Jinlong Jia; Weihua Wang (Shock and Vibration)
To understand differences of smooth and presplit blasting for the excavation of rock wells, two field experiments using these two techniques are implemented at the same test site, respectively. The ground vibrations induced by them have been monitored with the different distances through the corresponding devices. The vibration results illustrate that at the same monitoring distance and direction, peak particle velocities and dominant frequencies of vibration signals based on presplit blasting are both apparently lower than that based on smooth blasting. Meanwhile, with the increase of distance, the principle and mean frequencies based on smooth blasting always decrease, but these two frequencies based on presplit blasting might firstly decrease and then rise. In addition, frequency bands of energy distributions based on smooth blasting are more dispersive than that based on the presplit blasting at the same distance and direction. Lastly, the excavation qualities of rock wells with two techniques are also measured. The excavation results demonstrate that the contour quality and flatness of well bottom based on smooth blasting are better than that based on presplit blasting. Nevertheless, well depth based on presplit blasting is larger than that based on smooth blasting.